2002
DOI: 10.1016/s1044-0305(01)00362-2
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies of Zn-Ligand-Hexose diastereomers using ion mobility measurements and density functional theory calculations

Abstract: Ion mobility studies and density functional theory calculations were used to study the structures of [Zn/diethylenetriamine/Hexose/Cl] ϩ complexes in an effort to probe differences in the three-dimensional conformations. This information allows us to gain insight into the structure of these complexes before collisional activation, which is the first step in understanding the stereoselective dissociations observed under collisionally activated conditions. The collision cross sections obtained from the ion mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 35 publications
1
58
0
Order By: Relevance
“…It is generally considered that sugar conformations prefer to have functional groups in the equatorial orientation, that is, C1-conformation for hexopyranose 1 ThermoFinnigan Product Support Bulletin # 104. 2 Here B designates the fragment ion containing the nonreducing end sugar unit on the nonreducing end side of the glycosidic oxygen as indicated by Domon and Costello [12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is generally considered that sugar conformations prefer to have functional groups in the equatorial orientation, that is, C1-conformation for hexopyranose 1 ThermoFinnigan Product Support Bulletin # 104. 2 Here B designates the fragment ion containing the nonreducing end sugar unit on the nonreducing end side of the glycosidic oxygen as indicated by Domon and Costello [12].…”
Section: Resultsmentioning
confidence: 99%
“…We also acknowledge that other research groups have successfully distinguished anomers by mass spectrometry [13][14][15][16][17][18][19][20]. Among them, we are particularly interested in the report by Leavell et al [1] because they studied conformations of metal complexes of sugars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicated that small differences in drift times of individual precursor ions could be obtained both in the positive and negative ion modes, although full resolution of isomers from mixtures was not demonstrated. Using a different approach, Leavell et al combined computational methods and ion mobility mass spectrometry (IMMS) to examine the gas-phase ion structure of diethylenetriamine-derivatized sugars as zinc-ligand-hexose diastereomers [29]. Their studies were performed with derivatized reducing sugars hence multiple peaks were observed for individual sugars representing different configurations of complexes.…”
mentioning
confidence: 99%